PENGARUH HEATING TORCH TERHADAP TEMPERATURE DARI PERMUKAAN PLAT TEBAL 8 mm GRADE AH36 DENGAN PLAT 16 mm GRADE AH36 - Sumarsono Patti, Tito; Dasira, Alyuan; Zaki Prawira, Muhammad; Pradana Putra, Andrew (Fakultas Sains dan Teknologi Universitas Karimun, 2024)
This research aims to determine the effect of heating torch (Preheating) on ​​the surface temperature of 8mm thick plate grade AH36 with 16mm plate grade AH36, namely heating given to the base metal at the right temperature before welding. This research uses preheat temperatures of 80°C, 110°C, 140°C, and 170°C. Temperature is the temperature of a base metal around the area to be welded, namely before welding begins. Each plate sample is placed at a distance and similar heating conditions using a standard heating torch. The research results show that the thicker the plate, the temperature distribution on the surface is more even than the thinner plate, which can cause distortion. Observations were made regarding the time required to reach temperature variations of 80°C, 110°C, 140°C, and 170°C on the surface of the AH36 steel plate. . Plates that are 16mm thick will have a higher heat absorption capacity and take longer to reach the desired 65°/110° temperature. Whereas an 8mm plate may reach the desired temperature faster than a 16mm plate. The difference in plate thickness can also affect the heat distribution generated by the heating torch (burner). The 16mm plate may have better heat spreading ability than the 8mm plate may cause deformation.